High resolution energy dispersive spectroscopy mapping of planar defects in L12-containing Co-base superalloys. (1st May 2015) - Titus, Michael S.; Mottura, Alessandro; Babu Viswanathan, G.; Suzuki, Akane; Mills, Michael J.; Pollock, Tresa M.
Abstract: Local chemical fluctuations in the vicinity of superlattice intrinsic stacking faults (SISFs) have been observed via high resolution energy dispersive X-ray spectroscopy (EDS) mapping in new single crystal Co- and CoNi-base superalloys containing γ ′ -(L12 ) precipitates. The SISFs were formed during high temperature tensile creep at 900 °C. Chemical fluctuations were found to greatly influence the SISF energy, which was calculated from density functional theory in Co3 (Al, Ta, W) compounds at 0 K. The local SISF structure was found to be comprised of four D019 (0001) planes that were enriched in W and Ta, as revealed by high resolution scanning transmission electron microscopy (HRSTEM) imaging and EDS mapping. The precipitates were determined to accommodate up to 22% of the plastic deformation accrued during an interrupted creep test to 0.6% creep strain. The driving forces for segregation are discussed, and new models for shearing of the ordered precipitates are proposed.